PENERAPAN NILAI PANCASILA DALAM MENGATASI KRISIS MORALITAS GENERASI Z - Sutrisno, Nisa Wening Asih; Saputra, Inggar (Universitas Muhammadiyah Ponorogo, 2024)
Generation Z is a young generation who is connected to technology, intelligent, independent, confident and has global skills. However, generation Z is also experiencing the problem of a morality crisis, making them easily exposed to destructive content, low manners, minimal ethics in using social media and easily trapped by instant culture. For this reason, a Pancasila values approach is needed in overcoming the morality crisis. This research aims to determine the extent to which Pancasila values are applied at both conceptual and practical levels in overcoming the morality crisis that has hit generation Z. The research method uses a qualitative approach with descriptive methods. Data sources are observations, journals, books, articles and other relevant library materials. The results of the research are that family, school, religion, culture and technology greatly influence the prevention of the morality crisis among generation Z. The active involvement of parents, teachers, religious and community leaders, peers in using technology, especially the internet and social media, greatly influences the morality of generation Z. The conclusion of this research is that the application of Pancasila values in daily life which is influenced by family, school, religion, culture and technology can minimize the negative impact of technology and prevent a morality crisis in generation Z